Exploring Asherman’s Syndrome: Insights from a Comprehensive Literature Review - Kurza, Katarzyna; Kościuszko, Zuzanna; Sobiński, Adam; Czerwonka, Matylda; Podolec, Julianna; Ciraolo, Silvia; Agnieszka Kulczycka-Rowicka; Wojda, Joanna; Lesiczka-Fedoryj, Katarzyna; Walczak, Anna (Quality in Sport, 2025)
Purpose: This review aims to analyze the etiology, diagnosis, and management of Asherman’s Syndrome, focusing on advancements in treatment, emerging therapies, and persistent research gaps. Asherman’s Syndrome, characterized by intrauterine adhesions, leads to menstrual irregularities, infertility, and recurrent pregnancy loss. Materials and Methods: A comprehensive review of published studies on Asherman’s Syndrome was conducted, examining current diagnostic methods, treatment approaches, and therapeutic outcomes. Key sources included clinical trials, meta-analyses, and reviews from 1894 to 2021. Results: Endometrial trauma, often from dilation and curettage, is the primary cause of Asherman’s Syndrome. Diagnostic tools like three-dimensional ultrasound and hysteroscopy improve detection accuracy. Hysteroscopic adhesiolysis remains the gold standard treatment, with success rates of 70–85% in mild to moderate cases. Adjunct therapies, such as hormonal treatments and intrauterine devices, reduce adhesion recurrence. Emerging therapies like platelet-rich plasma and stem cell treatments show potential for improving endometrial regeneration and fertility but require further validation. Conclusions: While advances in hysteroscopy and regenerative medicine have enhanced outcomes for Asherman’s Syndrome, severe cases remain challenging due to high recurrence and poor reproductive results. Early diagnosis, multidisciplinary care, and standardized treatment protocols are essential. Further research is needed to validate emerging therapies, refine diagnostic tools, and improve quality of life for affected women.